Strong-plasticity TiAl intermetallic compound as well as preparation method and application thereof
Through the process of combining powder metallurgy and forging, a high-density cross nanotwin structure is formed, which solves the room temperature brittleness and complex preparation process of TiAl intermetallic compounds, and achieves high-performance strong plasticization and low-cost large-scale production.
Patent Information
- Application Number
- CN202411747141.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
It is difficult to achieve the intrinsic brittleness and high-temperature strength improvement of TiAl intermetallic compounds at room temperature, and the PST single crystal preparation process is complex, resulting in low yield and production efficiency, high cost, and difficult to achieve large-scale production and application.
Using a preparation process combining powder metallurgy and forging, TiAl intermetallic compound prealloy spherical powder is prepared by plasma rotary electrode atomization powder making method, thermal isostatic sintering and hot forging are carried out to form a high-density cross nanotwin structure. Achieve strong plasticization.
The high-density cross-nano twin strong plasticization of TiAl intermetallic compounds has excellent room temperature compression performance, compressive strength reaches 2500-2600 MPa, yield strength reaches 650-700 MPa, fracture strain reaches 35-40%, and It can achieve near-net forming of complex components, reduce production costs, and promote large-scale application.
Smart Images

Figure CN119220857A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of TiAl intermetallic compounds, and in particular relates to a high-plasticity TiAl intermetallic compound and a preparation method and application thereof. Background Art
[0002] TiAl intermetallic compounds have low density (~4.0 g / cm 3 ), high specific strength, high specific modulus, good high-temperature oxidation resistance and creep resistance and other excellent comprehensive properties, and are considered to be the most promising advanced high-temperature structural materials in the range of 700-1000℃. Although TiAl intermetallic compounds have initially achieved engineering applications in industrial fields such as aircraft engines and automobiles, there is still a certain gap before they can be widely used. The main reasons for this situation are the intrinsic brittleness at room temperature, the difficulty in further improving the high-temperature strength, and the poor forming performance. Among them, how to further effectively improve the strength and plasticity of TiAl intermetallic compounds is the most urgent basic problem to be solved.
[0003] Microstructure refinement is an effective way to achieve the strengthening and plasticization of TiAl intermetallic compounds. Alloying is one of the important methods to refine the microstructure of TiAl intermetallic compounds. Adding appropriate alloying elements can effectively refine the grain size. However, it is difficult to further achieve the strengthening and plasticization of TiAl intermetallic compounds by grain refinement strengthening. When the grain size or interlamellar spacing is reduced to submicron or even nanoscale, the microstructure of TiAl intermetallic compounds becomes unstable in the potential service temperature range (700-1000℃). Studies have found that when the grain size is reduced to nanoscale, the room temperature plasticity of TiAl intermetallic compounds is almost zero.
[0004] In 2016, Guang Chen et al. successfully prepared Ti-45Al-8Nb intermetallic compound 0°PST single crystal by using seedless directional solidification technology with controlled growth rate. Its room temperature tensile strength, yield strength and elongation can reach 978MPa, 708MPa and 6.9% respectively, which is the best comprehensive room temperature tensile performance of TiAl intermetallic compound at present; in addition, its creep performance at 900℃ is greatly improved compared with Ti-48Al-2Cr-2Nb which has been put into commercial application. The study found that the room temperature tensile deformation mechanism of Ti-45Al-8Nb intermetallic compound 0°PST single crystal is the formation of high-density deformation nanotwins, which is a typical nanotwin-strengthened TiAl intermetallic compound material. The specific preparation method of the PST single crystal is as follows: electromagnetic induction levitation melting of TiAl parent material ingot in a water-cooled copper crucible, and obtaining parent material rod by suction casting; using a four-mirror optical floating zone directional solidification furnace to directionally solidify the parent material rod, control the orientation of the TiAl intermetallic compound layer and obtain the PST crystal; and then using a vacuum heat treatment furnace to heat treat the PST crystal in the α single phase region and perform stress relief annealing to eliminate B2 phase segregation and residual stress, and finally form a TiAl intermetallic compound material with high strength and high plasticity.
[0005] However, it is difficult to directly prepare PST single crystals with complex shapes using the optical floating zone melting directional solidification method, and the prepared PST single crystals are small in size; in addition, the preparation process of TiAl intermetallic compound PST single crystals is complicated, resulting in low yield and production efficiency and high cost; these conditions make the large-scale production and application of TiAl intermetallic compound PST single crystals technically difficult. Summary of the invention
[0006] In view of the problems that it is difficult to further achieve strong plasticization of TiAl intermetallic compounds through fine grain strengthening and that TiAl intermetallic compound PST single crystals and components thereof are difficult to prepare, the present invention provides a strong plastic TiAl intermetallic compound and a preparation method and application thereof.
[0007] The technical solution of the present invention: A strong plastic TiAl intermetallic compound, wherein the atomic percentage concentration of Al is 44-47 at.%, the atomic percentage concentration of Nb is 7-10 at.%, the atomic percentage concentration of C is 0-0.5 at.%, and the balance is Ti.
[0008] Furthermore, the microstructure of the TiAl intermetallic compound is a near-γ microstructure, which mainly includes a γ phase and an α2 phase, wherein the content of the γ phase is 75-95%, and the content of the α2 phase is 5-25%.
[0009] Furthermore, the γ phase grain size of the TiAl intermetallic compound is 7~20 μm, and the γ phase grains contain a large number of cross-stacking faults; the TiAl intermetallic compound forms high-density cross-nano twins and at least two twins during plastic deformation at room temperature.
[0010] A method for preparing a high-density cross-nano twinned plasticized TiAl intermetallic compound comprises the following steps: Step 1: Packaging processing: The TiAl intermetallic compound pre-alloyed spherical powder is placed in a steel bag and vibrated to compact the powder. After the powder is filled, the bag is vacuum-sealed and welded to obtain a bag filled with TiAl powder. Step 2: Hot isostatic pressing sintering: The sealed and welded package obtained in step 1 is subjected to hot isostatic pressing sintering treatment, and after furnace cooling, the package is removed to obtain a TiAl ingot; Step 3: Hot forging: The TiAl ingot obtained in step 2 is subjected to two canning hot forging treatments, wherein the second hot forging direction is perpendicular to the first hot forging direction, to obtain a TiAl forging billet; Step 4: Heat treatment: The TiAl forging blank obtained in step 3 is heat treated, and after cooling, a high-density cross-nano twinned and plasticized TiAl intermetallic compound is obtained.
[0011] Furthermore, in step 1, the particle size distribution of the TiAl intermetallic compound pre-alloyed spherical powder is in the range of 60-220 μm, and the oxygen content of the TiAl intermetallic compound pre-alloyed spherical powder is controlled below 700 ppm.
[0012] Furthermore, the TiAl intermetallic compound pre-alloyed spherical powder in step 1 is prepared by a plasma rotating electrode atomization powder making method.
[0013] Furthermore, the specific preparation method of the plasma rotating electrode atomization powder making method is as follows: Before milling begins, the vacuum degree of the processing chamber must be reduced to less than 10 -3 Pa, and then fill with a mixture of argon and helium until the pressure in the processing chamber reaches 2×10 1 Pa, the oxygen content is less than 50 ppm; the diameter of the TiAl consumable electrode prepared by the conventional method according to the target alloy element content is 51~75 mm, it rotates at a speed of 30000~33000 rpm, the electrode feed speed is 0.5~1.2 mm / s, and the melting power of the plasma arc is 50~60 kW.
[0014] Furthermore, in step 2, the temperature of hot isostatic pressing sintering is 1200-1300°C, the pressure is 140-170 MPa, and the heat preservation and pressure holding time is 2-5 h.
[0015] Furthermore, the temperature of the hot forging in step three is 1200-1300°C, the deformation of the first hot forging is 30-60%, and the deformation of the second hot forging is 50-80%.
[0016] Furthermore, the heat treatment temperature in step 4 is 1200-1300°C, and the holding time is 1-5 h.
[0017] A high-density cross-nano twinned plasticized TiAl intermetallic compound is used in hot end components of power systems, including aerospace engines, gas turbines and automobile engines.
[0018] Beneficial effects of the present invention: The present invention adopts a preparation process combining powder metallurgy and forging to produce a large number of cross-stack faults in the γ grains of the obtained high-niobium TiAl intermetallic compound. These cross-stack faults can serve as effective nucleation sites for twins, so that the prepared TiAl intermetallic compound forms high-density cross-nano twins during deformation, thereby effectively achieving strong plasticization. The high-density cross-nano twinned strong plasticized TiAl intermetallic compound of the present invention has very excellent room temperature compression properties, with a compressive strength of 2500-2600 MPa, a yield strength of 650-700 MPa, and a fracture strain of 35-40%.
[0019] The present invention solves the problem of complex preparation process of TiAl intermetallic compound PST single crystal, can realize near-net forming of complex components such as aircraft engine blades, has high yield rate and production efficiency, low cost, and is easy to realize large-scale production and application.
[0020] The high-density cross-nano twinned plasticized TiAl intermetallic compound provided by the present invention is expected to be applied to aircraft engine blades, rocket engine nozzles, micro gas turbine turbines and blades, as well as hot end components such as automotive power system supercharger turbines and exhaust valves. It can effectively achieve lightweight equipment, improve the power output and combustion efficiency of various engines, and effectively promote energy conservation and emission reduction. It is a typical green and low-carbon field technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Band Contrast (diffraction band contrast) diagram obtained by EBSD (electron backscatter diffraction) analysis of the strong plastic TiAl intermetallic compound prepared in Example 2; Figure 2This is a phase content diagram obtained by EBSD analysis of the strong plastic TiAl intermetallic compound prepared in Example 2, in which red and purple are γ phases and green is α2 phase; Figure 3 This is a transmission electron microscope photograph of high-density cross-nano twins formed during the room temperature deformation process of the highly plastic TiAl intermetallic compound prepared in Example 2; Figure 4 The room temperature compression engineering stress-strain curve of the strong plastic TiAl intermetallic compound prepared in Example 2; Figure 5 This is a transmission electron microscope photograph of the cross-stacking faults in the γ grains of the high-ductility TiAl intermetallic compound prepared in Example 3. DETAILED DESCRIPTION
[0022] The technical solution of the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. The process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art. If not specifically specified, the raw materials used in the embodiments of the present invention can be obtained commercially; if not specifically specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.
[0023] Example 1 This embodiment provides a high-density cross-nano twinned strong plasticized TiAl intermetallic compound and a preparation method thereof.
[0024] In this embodiment, the atomic percentage concentration of Al in the TiAl intermetallic compound is 47 at.%, the atomic percentage concentration of Nb is 7 at.%, the atomic percentage concentration of C is 0 at.%, and the balance is Ti.
[0025] The preparation method of the high-density cross-nano twinned plasticized TiAl intermetallic compound in this embodiment comprises the following steps: Step 1: Packaging processing: The TiAl intermetallic compound pre-alloyed spherical powder is prepared by plasma rotating electrode atomization powder making method. The specific preparation method is as follows: Before milling begins, the vacuum degree of the processing chamber must be reduced to less than 10 -3 Pa, and then fill with a mixture of argon and helium until the pressure in the processing chamber reaches 2×10 1Pa, the oxygen content is less than 50 ppm; the diameter of the TiAl consumable electrode prepared by the conventional method according to the target alloying element content is 60 mm, it rotates at a speed of 30000 rpm, the electrode feed speed is 1.0 mm / s, the melting power of the plasma arc power is 50 kW, and the particle size distribution of the obtained TiAl intermetallic compound pre-alloyed spherical powder is in the range of 60~220 μm, and the oxygen content is controlled below 700 ppm.
[0026] The TiAl intermetallic compound pre-alloyed spherical powder is placed in a stainless steel sheath and vibrated to compact the powder. After the powder is filled, the sheath is vacuum-sealed and welded to obtain a sheath filled with TiAl powder. Step 2: Hot isostatic pressing sintering: The sealed package obtained in step 1 is subjected to hot isostatic pressing sintering treatment, the hot isostatic pressing sintering temperature is 1200°C, the pressure is 170 MPa, the heat preservation and pressure holding time is 5 h, and the package is removed after furnace cooling to obtain a TiAl ingot; Step 3: Hot forging: The TiAl ingot obtained in step 2 is subjected to two canning upsetting hot forging treatments, the hot forging temperature is 1200°C, the deformation amount of the first hot forging is 30%, the deformation amount of the second hot forging is 50%, and the direction of the second hot forging is perpendicular to the direction of the first hot forging, to obtain a TiAl forging billet; Step 4: Heat treatment: The TiAl forging blank obtained in step 3 is heat treated at a temperature of 1200°C for a holding time of 5 h, and then air-cooled to obtain a high-density cross-nano twinned, highly plasticized TiAl intermetallic compound.
[0027] The microstructure of the TiAl intermetallic compound prepared in this embodiment is a near-γ microstructure, mainly including γ phase and α2 phase, with a γ phase content of 95% and an α2 phase content of 5%. The γ phase grain size of the TiAl intermetallic compound is 7-20 μm, and the γ phase grains contain a large number of cross-stack faults; the TiAl intermetallic compound generates high-density cross-nano twins and forms at least two twins during plastic deformation at room temperature.
[0028] Example 2 This embodiment provides a high-density cross-nano twinned strong plasticized TiAl intermetallic compound and a preparation method thereof.
[0029] In this embodiment, the atomic percentage concentration of Al in the TiAl intermetallic compound is 45 at.%, the atomic percentage concentration of Nb is 8 at.%, the atomic percentage concentration of C is 0 at.%, and the balance is Ti.
[0030] The preparation method of the high-density cross-nano twinned plasticized TiAl intermetallic compound in this embodiment comprises the following steps: Step 1: Packaging processing: The same plasma rotating electrode atomization powder making method as in Example 1 was used to prepare TiAl intermetallic compound pre-alloyed spherical powder, the particle size distribution of the spherical powder was in the range of 60-220 μm, and the oxygen content was controlled below 700 ppm.
[0031] The TiAl intermetallic compound pre-alloyed spherical powder is placed in a stainless steel sheath and vibrated to compact the powder. After the powder is filled, the sheath is vacuum-sealed and welded to obtain a sheath filled with TiAl powder. Step 2: Hot isostatic pressing sintering: The sealed package obtained in step 1 is subjected to hot isostatic pressing sintering treatment, the hot isostatic pressing sintering temperature is 1250°C, the pressure is 150 MPa, the heat preservation and pressure holding time is 5 h, and the package is removed after furnace cooling to obtain a TiAl ingot; Step 3: Hot forging: The TiAl ingot obtained in step 2 is subjected to two canning upsetting hot forging treatments, the hot forging temperature is 1250°C, the deformation amount of the first hot forging is 40%, the deformation amount of the second hot forging is 70%, and the direction of the second hot forging is perpendicular to the direction of the first hot forging, to obtain a TiAl forging billet; Step 4: Heat treatment: The TiAl forging blank obtained in step 3 is heat treated at a temperature of 1250°C for a holding time of 2 h, and then air-cooled to obtain a high-density cross-nano twinned, highly plasticized TiAl intermetallic compound.
[0032] Figure 1 and Figure 2 They are respectively the Band Contrast (diffraction band contrast) diagram and the phase content diagram obtained by EBSD (electron backscattered diffraction) analysis of the high-density cross-nano twinned strongly plasticized TiAl intermetallic compound prepared in this embodiment, Figure 2 Red and purple are γ phase, and green is α2 phase; Figure 2 As shown, the microstructure of the TiAl intermetallic compound in this embodiment is a near-γ microstructure, mainly including γ phase and α2 phase, the γ phase content is 81%, and the α2 phase content is 19%. The γ phase grain size of the TiAl intermetallic compound is 7-20 μm.
[0033] Figure 3 TEM photo of high-density cross-nano twins formed during the deformation process of the high-density cross-nano twinned plasticized TiAl intermetallic compound prepared in this embodiment; Figure 3 As shown, the TiAl intermetallic compound of this embodiment forms high-density cross-nano twins and at least two twins during the plastic deformation process at room temperature.
[0034] Figure 4 The room temperature compression engineering stress-strain curve of the high-density cross-nano twinned plasticized TiAl intermetallic compound prepared in this embodiment is shown in FIG. Figure 4 It can be seen that the room temperature compressive strength, yield strength and fracture strain of the TiAl intermetallic compound of this embodiment can reach 2592 MPa, 672 MPa and 38.2% respectively.
[0035] Example 3 This embodiment provides a high-density cross-nano twinned strong plasticized TiAl intermetallic compound and a preparation method thereof.
[0036] In this embodiment, the atomic percentage concentration of Al in the TiAl intermetallic compound is 44 at.%, the atomic percentage concentration of Nb is 9 at.%, the atomic percentage concentration of C is 0.2 at.%, and the balance is Ti.
[0037] The preparation method of the high-density cross-nano twinned plasticized TiAl intermetallic compound in this embodiment comprises the following steps: Step 1: Packaging processing: The same plasma rotating electrode atomization powder making method as in Example 1 was used to prepare TiAl intermetallic compound pre-alloyed spherical powder, the particle size distribution of the spherical powder was in the range of 60-220 μm, and the oxygen content was controlled below 700 ppm.
[0038] The TiAl intermetallic compound pre-alloyed spherical powder is placed in a stainless steel sheath and vibrated to compact the powder. After the powder is filled, the sheath is vacuum-sealed and welded to obtain a sheath filled with TiAl powder. Step 2: Hot isostatic pressing sintering: The sealed package obtained in step 1 is subjected to hot isostatic pressing sintering treatment, the hot isostatic pressing sintering temperature is 1250°C, the pressure is 150 MPa, the heat preservation and pressure holding time is 4 hours, and the package is removed after furnace cooling to obtain a TiAl ingot; Step 3: Hot forging: The TiAl ingot obtained in step 2 is subjected to two canning upsetting hot forging treatments, the hot forging temperature is 1260°C, the deformation amount of the first hot forging is 50%, the deformation amount of the second hot forging is 70%, and the direction of the second hot forging is perpendicular to the direction of the first hot forging, to obtain a TiAl forging billet; Step 4: Heat treatment: The TiAl forging blank obtained in step 3 was heat treated at a temperature of 1250°C for a holding time of 2.5 h, and a high-density cross-nano twinned and strongly plasticized TiAl intermetallic compound was obtained after air cooling.
[0039] The microstructure of the TiAl intermetallic compound prepared in this embodiment is a near-γ microstructure, mainly including γ phase and α2 phase, with a γ phase content of 77% and an α2 phase content of 23%. The γ phase grain size of the TiAl intermetallic compound is 7-20 μm. Figure 5 The transmission electron microscope photograph of the cross stacking fault in the γ grains of the strong plastic TiAl intermetallic compound prepared in this embodiment is as follows: Figure 5 As shown, the γ phase grains contain obvious cross-stack faults; the TiAl intermetallic compound forms high-density cross-nano twins and at least two twins during the room temperature plastic deformation process.
[0040] Example 4 This embodiment provides a high-density cross-nano twinned strong plasticized TiAl intermetallic compound and a preparation method thereof.
[0041] In this embodiment, the atomic percentage concentration of Al in the TiAl intermetallic compound is 47 at.%, the atomic percentage concentration of Nb is 10 at.%, the atomic percentage concentration of C is 0.5 at.%, and the balance is Ti.
[0042] The preparation method of the high-density cross-nano twinned plasticized TiAl intermetallic compound in this embodiment comprises the following steps: Step 1: Packaging processing: The same plasma rotating electrode atomization powder making method as in Example 1 was used to prepare TiAl intermetallic compound pre-alloyed spherical powder, the particle size distribution of the spherical powder was in the range of 60-220 μm, and the oxygen content was controlled below 700 ppm.
[0043] The TiAl intermetallic compound pre-alloyed spherical powder is placed in a stainless steel sheath and vibrated to compact the powder. After the powder is filled, the sheath is vacuum-sealed and welded to obtain a sheath filled with TiAl powder. Step 2: Hot isostatic pressing sintering: The sealed package obtained in step 1 is subjected to hot isostatic pressing sintering treatment, the hot isostatic pressing sintering temperature is 1300°C, the pressure is 140 MPa, the heat preservation and pressure holding time is 2 h, and the package is removed after furnace cooling to obtain a TiAl ingot; Step 3: Hot forging: The TiAl ingot obtained in step 2 is subjected to two canning upsetting hot forging treatments, the hot forging temperature is 1300°C, the deformation amount of the first hot forging is 60%, the deformation amount of the second hot forging is 80%, and the direction of the second hot forging is perpendicular to the direction of the first hot forging, to obtain a TiAl forging billet; Step 4: Heat treatment: The TiAl forging blank obtained in step 3 is heat treated at a temperature of 1300°C for a holding time of 1 h, and then air-cooled to obtain a high-density cross-nano twinned, highly plasticized TiAl intermetallic compound.
[0044] The microstructure of the TiAl intermetallic compound prepared in this embodiment is a near-γ microstructure, mainly including γ phase and α2 phase, with a γ phase content of 75% and an α2 phase content of 25%. The γ phase grain size of the TiAl intermetallic compound is 7-20 μm, and the γ phase grains contain cross-stack faults; the TiAl intermetallic compound has high-density cross-nano twins and forms at least two twins.
[0045] Comparative Example 1 This comparative example provides a TiAl intermetallic compound with a low niobium content and a preparation method thereof.
[0046] In the comparative example, the atomic percentage concentration of Al in the TiAl intermetallic compound is 47 at.%, the atomic percentage concentration of Nb is 2 at.%, the atomic percentage concentration of C is 0.3 at.%, and the balance is Ti.
[0047] The preparation method of the TiAl intermetallic compound of this comparative example comprises the following steps: Step 1: Packaging processing: The same plasma rotating electrode atomization powder making method as in Example 1 was used to prepare TiAl intermetallic compound pre-alloyed spherical powder, the particle size distribution of the spherical powder was in the range of 60-220 μm, and the oxygen content was controlled below 700 ppm.
[0048] The TiAl intermetallic compound pre-alloyed spherical powder is placed in a stainless steel sheath and vibrated to compact the powder. After the powder is filled, the sheath is vacuum-sealed and welded to obtain a sheath filled with TiAl powder. Step 2: Hot isostatic pressing sintering: The sealed package obtained in step 1 is subjected to hot isostatic pressing sintering treatment, the hot isostatic pressing sintering temperature is 1300°C, the pressure is 160 MPa, the heat preservation and pressure holding time is 3 h, and the package is removed after furnace cooling to obtain a TiAl ingot; Step 3: Hot forging: The TiAl ingot obtained in step 2 is subjected to two canning upsetting hot forging treatments, the hot forging temperature is 1250°C, the deformation amount of the first hot forging is 40%, the deformation amount of the second hot forging is 60%, and the direction of the second hot forging is perpendicular to the direction of the first hot forging, to obtain a TiAl forging billet; Step 4: Heat treatment: The TiAl forging blank obtained in step 3 is heat treated at a temperature of 1250°C for a holding time of 2 h, and then air-cooled to obtain a TiAl intermetallic compound.
[0049] The microstructure of the TiAl intermetallic compound prepared in this comparative example is a near-γ microstructure, mainly including γ phase and α2 phase, with a γ phase content of 89% and an α2 phase content of 11%. The γ phase grain size of the TiAl intermetallic compound prepared in this comparative example is 10-20 μm, and there is basically no cross stacking fault in the γ phase grains; no high-density cross nano twins are formed during the room temperature plastic deformation process.
[0050] Comparative Example 2 The difference between this comparative example and Example 3 is that the heat treatment in step 4 of this comparative example adopts a traditional heat treatment process, which is as follows: Step 4: Heat treatment: After completing the hot forging in step three, the obtained TiAl forging billet is directly subjected to annealing heat treatment at a temperature of 850° C. for a holding time of 2 h. After furnace cooling, a TiAl intermetallic compound is obtained.
[0051] The microstructure of the TiAl intermetallic compound prepared in this comparative example is a dual-state microstructure, mainly including γ phase grains and γ / α2 lamellar clusters, the γ phase grain content is 75%, and the γ / α2 lamellar content is 25%. The γ phase grain size of the TiAl intermetallic compound prepared in this comparative example is 5-17 μm, and there are a large number of dislocations in the γ phase grains; high-density dislocations are formed during plastic deformation at room temperature.
[0052] The mechanical properties of the TiAl intermetallic compounds prepared in Example 1 to Example 4 and Comparative Example 1 to Comparative Example 2 were measured using GB / T 7314-2017. The results are shown in Table 1.
[0053] Table 1
[0054] By comparing the data in Table 1, it can be seen that the composition of the TiAl intermetallic compound of the present invention belongs to a high-niobium TiAl intermetallic compound, has a low stacking fault energy, and is conducive to the formation of twins during deformation. The present invention adopts a non-traditional preparation process combining powder metallurgy and forging to produce a large number of cross-stack faults in the γ grains of the obtained high-niobium TiAl intermetallic compound, and these cross-stack faults can serve as effective nucleation sites for twins, so that the prepared TiAl intermetallic compound forms high-density cross-nano twins during deformation, thereby effectively achieving strong plasticization and obtaining very excellent room temperature compression performance.
Claims
1. A high-plasticity TiAl intermetallic compound, characterized in that: The atomic percentage concentration of Al in the TiAl intermetallic compound is 44-47 at.%, the atomic percentage concentration of Nb is 7-10 at.%, the atomic percentage concentration of C is 0-0.5 at.%, and the balance is Ti.
2. A high-plasticity TiAl intermetallic compound according to claim 1, characterized in that: The microstructure type of the TiAl intermetallic compound is a near-γ microstructure, which mainly includes a γ phase and an α2 phase, wherein the content of the γ phase is 75-95%, and the content of the α2 phase is 5-25%.
3. A high-plasticity TiAl intermetallic compound according to claim 2, characterized in that: The γ phase grain size of the TiAl intermetallic compound is 7-20 μm, and the γ phase grains contain cross-stack faults; the TiAl intermetallic compound forms high-density cross-nano twins and at least two twins during room temperature plastic deformation.
4. A method for preparing a high-plasticity TiAl intermetallic compound as claimed in any one of claims 1 to 3, characterized in that: The steps include: Step 1: Packaging processing: The TiAl intermetallic compound pre-alloyed spherical powder is placed in a steel bag and vibrated to compact the powder. After the powder is filled, the bag is vacuum-sealed and welded to obtain a bag filled with TiAl powder. Step 2: Hot isostatic pressing sintering: The sealed and welded package obtained in step 1 is subjected to hot isostatic pressing sintering treatment, and after furnace cooling, the package is removed to obtain a TiAl ingot; Step 3: Hot forging: The TiAl ingot obtained in step 2 is subjected to two canning hot forging treatments, wherein the second hot forging direction is perpendicular to the first hot forging direction, to obtain a TiAl forging billet; Step 4: Heat treatment: The TiAl forging blank obtained in step 3 is heat treated, and after cooling, a high-density cross-nano twinned and plasticized TiAl intermetallic compound is obtained.
5. The method for preparing a high-plasticity TiAl intermetallic compound according to claim 4, characterized in that: Step 1: The particle size distribution of the TiAl intermetallic compound pre-alloyed spherical powder is in the range of 60-220 μm, and the oxygen content of the TiAl intermetallic compound pre-alloyed spherical powder is controlled below 700 ppm.
6. A method for preparing a high-plasticity TiAl intermetallic compound according to claim 4 or 5, characterized in that: Step 1: The TiAl intermetallic compound pre-alloyed spherical powder is prepared by a plasma rotating electrode atomization powder making method.
7. The method for preparing a high-plasticity TiAl intermetallic compound according to claim 6, characterized in that: The hot isostatic pressing sintering temperature in step 2 is 1200-1300°C, the pressure is 140-170 MPa, and the heat preservation and pressure holding time is 2-5 h.
8. The method for preparing a high-plasticity TiAl intermetallic compound according to claim 7, characterized in that: Step 3: The temperature of the hot forging is 1200-1300°C, the deformation of the first hot forging is 30-60%, and the deformation of the second hot forging is 50-80%.
9. The method for preparing a high-plasticity TiAl intermetallic compound according to claim 8, characterized in that: The heat treatment temperature in step 4 is 1200-1300°C, and the holding time is 1-5 h.
10. An application of the high-plasticity TiAl intermetallic compound according to any one of claims 1 to 3 in hot end components of a power system, characterized in that: The power systems include aerospace engines, gas turbines and automotive engines.
Citation Information
Patent Citations
A casting method for the preparation of thin-wall blades by using a titanium alloy containing trace amount of carbon
CN103060610A
High-fracture-toughness two-state titanium-aluminum-based composite material and preparation method thereof
CN109536760A
TiAl alloy with excellent deformation ability and preparation method thereof
CN109778005A
Nano twin crystal reinforced TiAl-based alloy and preparation method thereof
CN118186252A
Production of ti-al intermetallic compound
JP1994264203A
